Molecular characterization of Malaysian fowl adenovirus (FAdV) serotype 8b species E and pathogenicity of the virus in specific pathogen-free chicken - Sabarudin, Nur Syazana; Tan, Sheau Wei; Phang, Yuen Fun; Omar, Abdul Rahman (Korean Society of Veterinary Science, 2021)
Background: Inclusion body hepatitis (IBH) is an economically important viral disease primarily affecting broiler and breeder chickens. All 12 serotypes of fowl adenovirus (FAdV) can cause IBH. Objectives: To characterize FAdV isolates based on phylogenetic analysis, and to study the pathogenicity of FAdV-8b in specific-pathogen-free (SPF) chickens following virus inoculation via oral and intramuscular (IM) routes. Methods: Suspected organ samples were subjected to virus isolation and polymerase chain reaction (PCR) for FAdV detection. Hexon gene sequencing and phylogenetic analysis were performed on FAdV-positive samples for serotype identification. One FAdV-8b isolate, UPM/FAdV/420/2017, was selected for fiber gene characterization and pathogenicity study and was inoculated in SPF chickens via oral and IM routes. Results: The hexon gene phylogenetic analysis revealed that all isolates belonged to FAdV8b. The fiber gene-based phylogenetic analysis of isolate UPM/FAdV/420/2017 supported the grouping of that isolate into FAdV species E. Pathogenicity study revealed that, chickens infected with UPM/FAdV/420/2017 via the IM route had higher clinical score values, higher percent mortality, higher degree of the liver lesions, higher antibody response (p < 0.05), and higher virus shedding amounts (p < 0.05) than those infected via the oral route. The highest virus copy numbers were detected in liver and gizzard. Conclusions: FAdV-8b is the dominant FAdV serotype in Malaysia, and pathogenicity study of the FAdV-8b isolate UPM/FAdV/420/2017 indicated its ability to induce IBH in young SPF chickens when infected via oral or IM routes.